The Role Of Dividend Policy In Moderate The Influence Of Profitability And Liquidity On The Value Of Banking Companies Listed On The Indonesian Stock Exchange Period 2019–2022 - Muhammad Hidayat; Nagian Toni; Yeni Ariesa; Rosita Rosita (CV. Aksara Global Akademia, 2024)
The covid-19 pandemic in early 2020 has caused a decline in the value of banking companies in Indonesia. The limited space for people to move due to government policies has an impact on reducing economic activity and disrupting bank performance in providing credit. This study was conducted to determine the effect of profitability and liquidity on firm value with dividend policy as a moderating variable. The population in this study were 47 banking companies listed on the Indonesia Stock Exchange with an observation time of 4 years. The sampling method used in this study was purposive sampling, and the number of samples obtained was 12 banking companies. The data analysis method used is Moderated Regression Analysis (MRA) using SMART PLS 4. Based on the research results, profitability has a positive and significant effect on firm value while liquidity has a negative and significant effect on firm value. Meanwhile, dividend policy cannot moderate the effect of profitability and liquidity on the value of banking companies listed on the Indonesia Stock Exchange for the 2019-2022 period.